Macromol. Mater. Eng. 7/2018. Issue 7 (16th July 2018) - Liu, Yiwu; Liu, Junjie; Ding, Qian; Tan, Jinghua; Chen, Zhiquan; Chen, Junyi; Zuo, Xuri; Tang, Ao; Zeng, Kejian
Abstract : Back Cover : In article1800053 by Jinhua Tan and co‐workers, polyimide/graphene (DABPI/G) nanocomposites are prepared via in situ polymerization, with DABPI possessing a rigid planar molecular structure as a matrix, and a layered‐structure of graphene as a filler. The nanocomposites show high gas barrier properties due to the "dual‐plane" structure effect and have potential applications in flexible electronics encapsulation.